A Study On Predator-Prey Model For Competitive Corporation - MOHAMED SABRI, INTAN NURJANNAH; JACOB, KAVIKUMAR (Enhanced Knowledge in Sciences and Technology, 2021)
Predator-prey models have been used for years to model animal populations. In recent years, researchers started applying to economic-related problem. The purpose of this research is to examine the competitive corporations in Malaysia. This report examines the basic Lotka-Volterra predator-prey model and two predator and one prey model. The numerical dynamical behavior of the model by regression techniques for estimating parameters of the predator-prey model has been discussed. The obtained results must be significant for the further analysis. The used of logistic equation is to deal with the possibility of predicting long-term development based on logistic curves. Finally, Hopf Bifurcation analysis will be performed with respect to parameter values of approximate Lotka-Volterra predator-prey model.